Clinical Signs to Categorize Shock and Target Vasoactive Medications in Warm Versus Cold Pediatric Septic Shock*. Issue 12 (December 2020) - Walker, Sarah B.; Conlon, Thomas W.; Zhang, Bingqing; Mensinger, Janell L.; Fitzgerald, Julie C.; Himebauch, Adam S.; Glau, Christie; Nishisaki, Akira; Ranjit, Suchitra; Nadkarni, Vinay; Weiss, Scott L.
Abstract : Objectives: Determine level of agreement among clinical signs of shock type, identify which signs clinicians prioritize to determine shock type and select vasoactive medications, and test the association of shock type-vasoactive mismatch with prolonged organ dysfunction or death (complicated course). Design: Retrospective observational study. Setting: Single large academic PICU. Patients: Patients less than 18 years treated on a critical care sepsis pathway between 2012 and 2016. Interventions: None. Measurements and Main Results: Agreement among clinical signs (extremity temperature, capillary refill, pulse strength, pulse pressure, and diastolic blood pressure) was measured using Fleiss and Cohen's κ. Association of clinical signs with shock type and shock type-vasoactive mismatch (e.g., cold shock treated with vasopressor rather than inotrope) with complicated course was determined using multivariable logistic regression. Of 469 patients, clinicians determined 307 (65%) had warm and 162 (35%) had cold shock. Agreement across all clinical signs was low (κ, 0.25; 95% CI, 0.20–0.30), although agreement between extremity temperature, capillary refill, and pulse strength was better than with pulse pressure and diastolic blood pressure. Only extremity temperature (adjusted odds ratio, 26.6; 95% CI, 15.5–45.8), capillary refill (adjusted odds ratio, 15.7; 95% CI, 7.9–31.3), and pulse strength (adjusted odds ratio, 21.3; 95% CI, 8.6–52.7) were associated with clinician-documented shock type. Of the 86 patients initiated on vasoactive medications during the pathway, shock type was discordant from vasoactive medication (κ, 0.14; 95% CI, –0.03 to 0.31) and shock type-vasoactive mismatch was not associated with complicated course (adjusted odds ratio, 0.3; 95% CI, 0.1–1.02). Conclusions: Agreement was low among common clinical signs used to characterize shock type, with clinicians prioritizing extremity temperature, capillary refill, and pulse strength. Although clinician-assigned shock type was often discordant with vasoactive choice, shock type-vasoactive mismatch was not associated with complicated course. Categorizing shock based on clinical signs should be done cautiously. Abstract : Supplemental Digital Content is available in the text.